Media events and cosmopolitan fandom: 'Playful nationalism' in the Eurovision Song Contest. (November 2018) - Kyriakidou, Maria; Skey, Michael; Uldam, Julie; McCurdy, Patrick
Academic literature on media events is increasingly concerned with their global dimensions and the applicability of Dayan and Katz's theoretical concept in a post-national context. This article contributes to this debate by exploring the Eurovision Song Contest (ESC) as a global media event. In particular, we employ a perspective from 'inside the media event', drawing upon empirical material collected during the 2014 Eurovision final in Copenhagen and focusing on the experiences of fans attending the contest. We argue that the ESC as a media event is experienced by its fans as a cosmopolitan space, open and diverse, whereas national belonging is expressed in a playful way tied to the overall visual aesthetics of the contest. However, the bounded and narrow character of participation render this cosmopolitan space rather limited.